In‐Operando Neutron Diffraction Studies of Transition Metal Hydrogen Storage Materials. Issue 1 (13th September 2012) - Kamazawa, Kazuya; Aoki, Masakazu; Noritake, Tatsuo; Miwa, Kazutoshi; Sugiyama, Jun; Towata, Shin‐ichi; Ishikiriyama, Mamoru; Callear, Samantha K.; Jones, Martin O.; David, William I. F.
<x xml:space="preserve">Abstract</x> Neutron diffraction studies of hydrogen absorption and desorption (non‐isotopically enriched) in the metal hydride Ti25Cr50V20Mo5Hx, reveal the origin of the reduction in capacity exhibited by this material on cycling. The sequestered hydrogen is principally located in the octahedral and tetrahedral interstitial sites in the basal plane, while local diffusion along the unique tetragonal axis appears to be preferred. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>